Cellular contribution to left and right atrial dysfunction in chronic arterial hypertension in pigs. (29th November 2020) - Jin, Ge; Manninger, Martin; Adelsmayr, Gabriel; Schwarzl, Michael; Alogna, Alessio; Schönleitner, Patrick; Zweiker, David; Blaschke, Florian; Sherif, Mohammad; Radulovic, Snjezana; Wakula, Paulina; Schauer, Sylvia; et al.
Abstract: Aims: Atrial contractile dysfunction contributes to worse prognosis in hypertensive heart disease (HHD), but the role of cardiomyocyte dysfunction in atrial remodelling in HHD is not well understood. We investigated and compared cellular mechanisms of left (LA) and right atrial (RA) contractile dysfunction in pigs with HHD. Methods and results: In vivo electrophysiological and magnetic resonance imaging studies were performed in control and pigs treated with 11‐deoxycorticosterone acetate (DOCA)/high‐salt/glucose diet (12 weeks) to induce HHD. HHD leads to significant atrial remodelling and loss of contractile function in LA and a similar trend in RA (magnetic resonance imaging). Atrial remodelling was associated with a higher inducibility of atrial fibrillation but unrelated to changes in atrial refractory period or fibrosis (histology). Reduced atrial function in DOCA pigs was related to reduced contraction amplitude of isolated LA (already at baseline) and RA myocytes (at higher frequencies) due to reduced intracellular Ca release (Fura 2‐AM, field stimulation). However, Ca regulation differed in LA and RA cardiomyocytes: LA cardiomyocytes showed reduced sarcoplasmic reticulum (SR) [Ca], whereas in RA, SR [Ca] was unchanged and SR Ca 2+ ‐ATPase activity was increased. Sodium–calcium exchanger (NCX) activity was not significantly altered. We used ORM‐10103 (3 μM), a specific NCX inhibitor to improve Ca availability in LA and RA cardiomyocytes from DOCA pigs. Partial inhibition of NCX increased Ca 2+ transient amplitude and SR Ca in LA, but not RA cells. Conclusions: In this large animal model of HHD, atrial remodelling in sinus rhythm in vivo was related to differential LA and RA cardiomyocyte dysfunction and Ca signalling. Selective acute inhibition of NCX improved Ca release in diseased LA cardiomyocytes, suggesting a potential therapeutic approach to improve atrial inotropy in HHD.